Seroprevalence and Molecular Analysis of Bovine Leukemia Virus in Kazakhstan - Saltanat Mamanova; Ainur Nurpeisova; Elvira Bashenova; Saira Kaimoldina; Vladimir Kirpichenko; Perizat Akshalova; Aiken Karabassova; Malik Yussupov; Akzhigit Mashzhan; Dauriya Tazhbayeva; Zhandos Abay; Marzena Rola-Luszczak; et al. (Viruses, 2025)
Bovine leukemia virus (BLV) remains a major concern for cattle industries worldwide due to its persistent nature, economic impact, and challenges in control. In this study, we conducted a comprehensive nationwide survey of BLV in Kazakhstan between 2014 and 2024, utilizing serological diagnostics to assess prevalence and characterize viral genotypes (2024). A total of 433,537 serum samples were screened by agar gel immunodiffusion (AGID), revealing an overall seroprevalence of 5.87%, with the highest rates observed in the North Kazakhstan, Kostanay, and East Kazakhstan regions. In 2024, a targeted analysis of 3736 serum and 536 whole blood samples across 17 regions was performed using AGID, ELISA, real-time PCR, and nested PCR. ELISA demonstrated higher sensitivity than AGID (10.4% vs. 8.2%), confirmed by statistical correlation (r = 0.97, p < 0.001) and a Wilcoxon signed-rank test (p = 0.026). Real-time PCR detected BLV DNA in 4.7% of samples, with the highest positivity in the East Kazakhstan and Abai regions, confirming active viral circulation. Validation of a domestically developed AGID diagnostic kit showed full concordance with commercial assays (IDEXX, IDvet), supporting its use in national surveillance programs. These findings highlight the endemic status of BLV in Kazakhstan. Molecular analysis of sequenced isolates revealed the presence of genotype G-7, consistent with strains circulating in neighboring countries. Together, these results underscore the importance of integrated serological and molecular approaches for effective monitoring and control.